A socio-economic assessment on the selected borrowers of micro financial institutions in Tacloban City. - Basog, Lenny Jane (Lenny Jane Basog [and] Mark Louie Serrano, 2010)
The purpose of this study is to identify and determine the socio-economic impact of micro financial institutions to its borrowers in Tacloban City.